2013
DOI: 10.1063/1.4824393
|View full text |Cite
|
Sign up to set email alerts
|

Constrained large-eddy simulation of wall-bounded compressible turbulent flows

Abstract: A constrained large-eddy simulation (CLES) approach is developed for wall-bounded compressible turbulent flows based on its incompressible analogue [Chen et al., “Reynolds-stress-constrained large-eddy simulation of wall-bounded turbulent flows,” J. Fluid Mech. 703, 1–28 (2012)]. In the new CLES approach, both the subgrid-scale (SGS) stress and the SGS heat flux are decomposed into an averaged part and a fluctuating part in the near-wall region with the mean SGS stress and heat flux constrained by prescribed R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 45 publications
0
37
0
Order By: Relevance
“…These model coefficients can be prescribed empirically or calculated instantaneously through a dynamic procedure. For details of the derivation of the DC-SGS models, readers are referred to the article by Chen et al [1] for incompressible flow and the one by Jiang et al [6] for compressible flow. In the rest region of the flow domain, traditional Smagorinsky models for the SGS stress and SGS heat flux can be utilized [9].…”
Section: Constrained Large Eddy Simulationmentioning
confidence: 99%
See 3 more Smart Citations
“…These model coefficients can be prescribed empirically or calculated instantaneously through a dynamic procedure. For details of the derivation of the DC-SGS models, readers are referred to the article by Chen et al [1] for incompressible flow and the one by Jiang et al [6] for compressible flow. In the rest region of the flow domain, traditional Smagorinsky models for the SGS stress and SGS heat flux can be utilized [9].…”
Section: Constrained Large Eddy Simulationmentioning
confidence: 99%
“…(1)- (4). Considering that both the Reynolds stress and the Reynolds heat flux are poorly estimated by traditional LES approaches in the near-wall region of wall-bounded compressible flows, Jiang et al introduced a dual-constraint SGS (DC-SGS) model for LES of such flows [6]. The formulations of the DC-SGS models are reviewed briefly as follows.…”
Section: Constrained Large Eddy Simulationmentioning
confidence: 99%
See 2 more Smart Citations
“…[46], the variation process under an SGS dissipation constraint is helpful in improving the performance of a mixed dynamic model for simulation of driven and decaying isotropic turbulence. It was also shown that the inclusion of the near-wall Reynolds stress (and heat flux) constraint(s) in the SGS modeling allows the LES technique to simulate wall-bounded turbulent flows at moderate grid resolutions with promising accuracy [47,48]. Although the physical mechanism of the interplay between energy and helicity cascades still remains unclear, the effect of helicity has been taken into account for turbulence modeling.…”
Section: Introductionmentioning
confidence: 99%